Kebijakan HIV/AIDS dan Prevention Mother To Child Transmision (PMTCT) di Indonesia - Anugrahini, Triyanti (UI Scholars Hub, 2008)
The various policies which related to HIV/AIDS in Indonesia is continue to be developed in line with the increasing number of HIV/AIDS cases in Indonesia since the cases were first found in 1987 By using the framework of a retrospective policy analysis (analysis of policy), this paper will review the formulation of the policy and its contents, seen from several dimensions that are interconnected with one another, ie the contents of the policy (content), national and international contextual conditions (context), policy-making (process) and the actors that play the role and influence in the policy-making (actors) Policy analysis is described based on three periods. The first period (1994-2002) the Indonesian Government developed the National Strategy on HIV/AIDS policy that applied nationally, and the involvement of various sectors In the second period (2003-2004), there was a revision of the National Strategy on HIV/AIDS because the transformation of national and international contextual conditions The increasing numbers of HIV/AIDS cases by the year 2005 in Indonesia, has accelerate the desire of government to formulate the PMTCT strategy more